1970
DOI: 10.1104/pp.45.3.330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photoperiod and End-of-Day Light Quality on Alkaloids and Phenolic Compounds of Tobacco

Abstract: Tobacco plants (Nicotiana tabacum L.) were grown on long or short photoperiods followed by 5 minutes of red or far red radiation each day. Plants that received 16-hour photoperiods had a significantly higher concentration of total alkaloids and total phenolics than those that received 8-hour photoperiods. Significantly higher total alkaloid content was found in plants that received red rather than far red radiation last each day. Within each photoperiod, plants that received far red had higher concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…For duckweed Umemoto (13) reported that chlorogenic acid accumulation depended on the daylength: shorter periods than a 12-h photoperiod did not cause accumulation, while the acid was accumulated in proportion to daylengths longer than 12 h. This is similar to the situation in the leaves of S. occidentalis (Fig. 6).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…For duckweed Umemoto (13) reported that chlorogenic acid accumulation depended on the daylength: shorter periods than a 12-h photoperiod did not cause accumulation, while the acid was accumulated in proportion to daylengths longer than 12 h. This is similar to the situation in the leaves of S. occidentalis (Fig. 6).…”
Section: Methodssupporting
confidence: 71%
“…In 10 experiments with plants which had been in SD (8-h light, 16-h darkness) for 5 days the average increase of absorbancy at 450 nm (see Fig. 5 (4,7,(11)(12)(13)15). The accumulation pattern of the phenolics (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the plants were grown at different times of the year: the KD plants were grown from April to July, while the OX plants were grown from November to February. Long days are known to favor alkaloid production (Tso et al, 1970). However, the NCRs in vector control lines used in both OX and KD experiments were similar (2.96% and 2.62%) regardless of the growing season, which is in agreement with the NCRs of less than 3.0% that were reported for commercial tobacco lines (Jack et al, 2007).…”
supporting
confidence: 77%
“…However, if soil N content is relatively high, additional water increases nicotine concentration as the N uptake under these circumstances exceeds the dilution effect (Biglouei et al, 2010). Moreover, a prolonged photoperiod or short-wavelength sunlight significantly increased nicotine concentration (Tso et al, 1970;Kartusch and Mittendorfer, 1990), but very strong or very weak light intensity led to the highest nicotine concentration in tobacco leaf (Tso, 1990). …”
Section: Introductionmentioning
confidence: 99%